2017
DOI: 10.1097/wad.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Time, Sex, Gender, History, and Dementia

Abstract: A growing body of epidemiologic evidence indicates a decline in the incidence or prevalence of dementia in high income countries in the past 25 years. In this commentary, I first suggest that the decline in the incidence or prevalence of dementia is not explained completely by the factors considered so far, and that a broader historical perspective may be needed. Second, I suggest that the overall declining trend may conceal trends in opposite directions for the two major subtypes of dementia, the neurovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…However, some European studies have reported a higher incidence among women at older ages, 216,217 and one study from the United Kingdom reported higher incidence for men 218 . Differences in the risk of dementia between men and women may therefore depend on age and/or geographic region 219,220 …”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…However, some European studies have reported a higher incidence among women at older ages, 216,217 and one study from the United Kingdom reported higher incidence for men 218 . Differences in the risk of dementia between men and women may therefore depend on age and/or geographic region 219,220 …”
Section: Prevalencementioning
confidence: 99%
“…218 Differences in the risk of dementia between men and women may therefore depend on age and/or geographic region. 219,220 If there is a difference in the risk of Alzheimer's or other dementias between men and women, there are a number of potential biological and social explanations. 219,221 One explanation may be differences in the distribution of or even the effect of risk factors for dementia between men and women.…”
Section: Differences Between Women and Men In The Prevalence And Riskmentioning
confidence: 99%
“…Though there are more women than men living with dementia, Mielke points out that the incidence is not always higher for women than men and that "sex and gender differences in the incidence of AD dementia may depend on the time period and geographical region" (2018, p. 2). It is notable that intersectional and feminist approaches to dementia are now exploring relationships between sex, gender and dementia, and the impact of these on care and public policy (Bartlett et al, 2018;Mielke, 2018;Sandberg, 2018;Rocca, 2017). Though full discussion of the significance of gender in children's books about dementia is beyond the scope of this paper, it is important to note that cultural narratives such as picturebooks do not simply reflect real-world statistics and experiences, but also help to shape the ways in which we understand dementia (including its relationship to gender).…”
Section: Selecting and Analysing Picturebooks About Dementiamentioning
confidence: 99%
“…These projections were made under the simple assumption that the age‐ and sex‐specific prevalence would remain stable over 25 years. However, the burden of diseases may be modified over time by human practices, including public health interventions and medicine . Rossi and colleagues have suggested that the successful implementation of smoking cessation interventions in the United States may lead to an increase in the projected number of persons who will suffer from PD by 2040 .…”
mentioning
confidence: 99%
“…However, the burden of diseases may be modified over time by human practices, including public health interventions and medicine. 2 Rossi and colleagues have suggested that the successful implementation of smoking cessation interventions in the United States may lead to an increase in the projected number of persons who will suffer from PD by 2040. 3 Their revised projections were based on a projected 46.2% increase in the population 50 years old and a 59.8% reduction in the percentage of smokers 50 years old between 2000 and 2040.…”
mentioning
confidence: 99%